Knowledge of future dental practitioners towards oral cancer: exploratory findings from a public university in Malaysia - Bhagavathula, Akshaya Srikanth; Zakaria, Nazrin; Jamshed, Shazia Qasim (Hindawi Publishing Corporation, 2015)
Objective. To assess knowledge and awareness of oral cancer in the early identification of risk factors among undergraduate dental students. Methods. A total of 162 undergraduate (third, fourth, and fifth year) dental students at International Islamic University, Malaysia, were approached to participate in the study, and those who agreed were administered. A 9-item pretested questionnaire contains questions on oral examination, oral cancer risk factors, and requests for further information. Descriptive statistics were conducted using chi-square testing. Results. The response rate of the study was 70.3% (114/162), with 26 (22.8%) males and 88 (77.2%) females. All undergraduate dental students were familiar with examining the oral mucosa of their patients and most were likely to advise patients about the risk factors for developing oral cancer (98.2%). Nearly one-third (32.4%) of students reported examining patients with oral lesions as early signs for oral cancer (